Environmental Disputes Without The Principle Of Strict Liability After The Job Creation Law Regime - Lalu Aria Nata Kusuma (Veteran Law Review, 2023)
The 1945 Constitution of the Republic of Indonesia in Article 28 H paragraph 1 states that a good and healthy environment is a human right and a constitutional right for every Indonesian citizen. The form of environmental protection is then accommodated, one of which is in Article 88 of Law Number 32 of 2009 concerning Environmental Protection and Management (UU PPLH) through the Strict Liability principle or what is called absolute responsibility for every party who pollutes and destroys the environment caused by Hazardous and Toxic Materials (B3) and B3 waste without the need for proof of the element of error first. However, after the enactment of Law Number 11 of 2020 concerning Job Creation, absolute responsibility for perpetrators of environmental destruction has disappeared due to the abolition of the phrase "without the need for proof of the element of fault" so that accountability is based on fault (liability based on fault). The purpose of this study was to determine the impact of the abolition of the principle of strict liability in the settlement of environmental disputes in Indonesia. The research method used is normative legal research using statutory, conceptual, and case approaches. Based on the results of the study, it is shown that the abolition of strict liability in the PPLH Law will burden victims in environmental disputes, especially ordinary people, to ask for accountability because of the complexity of proving the element of error in industrial activities that use high technology and is directly related to B3 (ultrahazardous activity and abnormally dangerous).